‘We need to be supported so that we are able to also provide better care’ Well-being and self-care needs among health workers providing HIV care to children and adolescents in Africa: Qualitative findings from 12 high HIV-prevalence African countries - Carley Citron; Lesley Gittings; Megan Oberwasserlechner; Agnes Ronan; Luann Hatane (PLoS ONE, 2026)
Frontline healthcare workers providing HIV services to children, adolescents and their families in Africa face significant stressors and well-being related challenges. These in turn may also impact their ability to provide high-quality, compassionate care. Despite healthcare providers’ central role in the delivery of care and support for others, there is limited research exploring their well-being and self-care. This study examined the well-being and self-care-related challenges and needs among healthcare workers providing HIV services to children, adolescents and their caregivers in Africa. A qualitative study design was employed, including participatory priority-setting and focus group discussions with 801 providers across 24 sites in 12 high HIV-prevalence African countries. Data were thematically analysed and Orem’s Theory of Self-Care and the Self-Care Matrix were employed to guide the interpretation and organization of findings. The study identified four major themes. First, participants described burnout and personal struggles as well-being related challenges. Second, they described the belief that addressing these challenges was important for their own well-being, as well as the well-being of their patients. Third, awareness of healthcare worker well-being, alongside effective communication are important contributors to a healthier workforce. Lastly, several interventions were suggested, including fostering teamwork, providing education, and offering psychosocial support within the workplace. Findings emphasize the critical need for tailored interventions that can inform future practices and strategies for healthcare worker well-being. Ultimately, these interventions are crucial for better supporting healthcare providers, enhancing their well-being, and addressing the ongoing challenges in HIV care to children and adolescents in Africa.